The Effect of Financial Literation on Students's Personal Financial Planning in Malang (Case Study on Pesantren Luhur Malang and Pesantren Al-Barakah Malang) - Grisvia Agustin; Desy Erlanda Pratasari (Hasanuddin Economics and Business Review, 2020)
Financial literacy is very important because it is needed for financial planning so that people can manage their finances more optimally. However, according to the FSA, Indonesia has a low level of financial literacy, so there is a need for research on differences in financial planning in Pesantren Luhur Malang which obtain financial literacy studies from Kitab Kuning and halaqah (a seminar of scientific study) with financial planning in Pesantren Al-Barakah Malang which gain financial literacy from Kitab Kuning only. This study aims to determine the effect of financial literacy on the financial planning of students of Pesantren Luhur Malang and students of Pesantren Al-Barakah Malang, as well as differences in financial literacy and financial planning between students Pesantren Luhur Malang and students of Pesantren Al-Barakah Malang. This study uses a descriptive quantitative approach, with two variables financial literacy and financial planning, using simple linear regression analysis and independent-sample t-test. Sampling using purposive sampling with a total sample of 52 students consisting of 26 students of Pesantren Luhur Malang and 26 students of Pesantren Al-Barakah Malang. Based on data analysis, are known that (1) financial literacy has an effect on financial planning in students of Pesantren Luhur Malang and students  Pesantren Al-Barakah Malang (2) there is a  difference between the financial literacy of students of Pesantren Luhur Malang and students of Pesantren Al-Barakah Malang. (3) there are differences in the financial planning of students  Pesantren Luhur Malang and students  Pesantren Al-Barakah Malang.